Seasonality in the cross-shelf physical structure of a temperate shelf sea and the implications for nitrate supply. (October 2019) - Ruiz-Castillo, Eugenio; Sharples, Jonathan; Hopkins, Jo; Woodward, Malcolm
Highlights: We address nutrient supplies into the interior of a wide, temperate shelf sea. Riverine inputs contribute about 30% of the nitrate available for the spring bloom. In the bottom layer, high salinity and nutrient-rich waters are transported on-shelf during summer. On-shelf transport and recycling are responsible for the seasonal increase in bottom water nitrate. Abstract: We address a long-standing problem of how nutrients are transported from the shelf edge and from rivers to support regular, seasonal primary production in the interior of a wide, temperate, shelf sea. Cross-shelf sections of hydrography and nutrients, from a series of cruises between March 2014 and August 2015, along with time series of river discharge and river nutrient load are used to assess the seasonality of cross-shelf transports. Riverine nitrogen inputs are estimated to account for 30% of the nitrate available for the spring bloom on the inner shelf, and 10% in the mid- to outer-shelf. In the bottom layer in summer, high salinity, nutrient-rich waters are transported on-shelf as a result of wind-driven Ekman transport, cross-shelf pressure gradients and/or internal tidal wave Stoke's drift. In the centre of the shelf this advection is responsible for 25% of the increase in bottom water nitrate seen between April and November 2014. The remaining nitrate increase suggests that about 50–62% of the nitrogen fixed into organic material during spring, summer and autumn phytoplankton growth is recycled in the bottom water over the 12 months between March 2014 and March 2015. In winter, when the water column is vertically mixed, there is a weak net off-shelf transport of about 1 m 2 s −1, possibly driven by a reversal of the horizontal density gradient caused by excess cooling of shallower shelf waters. Overall, shelf nitrate concentrations are maintained by a combination of riverine supply, recycling of organic material, and summer on-shelf transports. We suggest that the main driver of inter-annual variability in pre-spring nitrate concentrations is variability in the depth of the winter mixed layer over the shelf slope.